Concurrent Inheritance of Deletional a-thalassaemia in Malays with HbE Trait - Teh, L.K.; George, E.; Lai, M.I.; Ahmad, R.; Zakaria, Z.; Tan, J. (2009)
Introduction: HbE is the commonest beta haemoglobin (Hb) variant in Southeast Asia. It causes a reduction in synthesis of the beta-globin E chain. Studies indicate HbE coinherited with a-thalassaemia leads to milder clinical phenotype. This study investigates the commitant inheritance of a-thalassaemia in Malays with HbE. Methods: Four hundred and fourteen (414) blood samples were screened for haemoglobinopathy using primarily the first three steps of the BHES (B) blood counts, blood film; (H), HPLC; (E) electrophoresis; (S), stability protocol. Complete blood cell analyser, Hb typing with cation exchange high-performance liquid chromatography (HPLC) and Hb electrophoresis at an alkaline pH (pH 8.5) Forty-five (10.9%) were identified as HbE trait and DNA analysis was done for deletional a-thalassaemia using a single-tube multiplex-PCR assay. Results: Among the 45 subjects with HbE trait, 4 (8.9%) were found to have alpha-thalassaemia -2 (a) (a-37 kb deletion) and 1 (2.2%) the alpha-thalassaemia-1 (a0) (---SEA 20.5 kb deletion) defects respectively. Discussion: These findings show that 11.1% of Malays with HbE inherit alpha-thalassaemia concurrently. The most prevalent interaction found was a double heterozygote for HbE /a-thalassaemia 2, followed by HbE/a-thalassaemia 1. Conclusion: Molecular screening of deletional a-thalassaemia identified its concurrent inheritance in 11.1%o of Malays who were HbE carriers. This information will guide genetic counseling and the planning of treatment modalities in patients with HbE alpha-thalassaemia.